2015
DOI: 10.1080/17441692.2015.1047391
|View full text |Cite
|
Sign up to set email alerts
|

Stigma, shame and women's limited agency in help-seeking for intimate partner violence

Abstract: In Tanzania, 44% of women experience intimate partner violence (IPV) in their lifetime, but the majority never seeks help, and many never tell anyone about their experience. Even among the minority of women who seek support, only 10% access formal services. Our research explored the social and structural barriers that render Tanzanian women unable to exercise agency in this critical domain of their lives. We collected qualitative data in three regions of Tanzania through 104 key informant interviews with duty … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

9
132
1
8

Year Published

2017
2017
2024
2024

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 142 publications
(150 citation statements)
references
References 14 publications
9
132
1
8
Order By: Relevance
“…Women in both sites reported that they would like to receive more help, but when asked whom they would like to receive help from, many women stated members of their family rather than police or health centres. These preferences are likely to still exist as the qualitative study in Tanzania by McCleary-Sills and colleagues documented how women seek help from various informal sources first before approaching formal services [32]. Women’s first port of call was the family, at times the partner’s family, where the support given varied from assistance in mediation between the woman and her partner to advice including being told to tolerate the abuse.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Women in both sites reported that they would like to receive more help, but when asked whom they would like to receive help from, many women stated members of their family rather than police or health centres. These preferences are likely to still exist as the qualitative study in Tanzania by McCleary-Sills and colleagues documented how women seek help from various informal sources first before approaching formal services [32]. Women’s first port of call was the family, at times the partner’s family, where the support given varied from assistance in mediation between the woman and her partner to advice including being told to tolerate the abuse.…”
Section: Discussionmentioning
confidence: 99%
“…Women’s first port of call was the family, at times the partner’s family, where the support given varied from assistance in mediation between the woman and her partner to advice including being told to tolerate the abuse. It is only if the issue remains unresolved that it is then acceptable for women to go to external sources of support such as local or religious leaders [32]. A qualitative study on health care worker perceptions about intimate partner violence, conducted in DSM, highlighted their frustrations at women’s reluctance to disclose abuse despite their being given evidence from the victims’ families or friends.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations